3q-70=q+26

Simple and best practice solution for 3q-70=q+26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3q-70=q+26 equation:


Simplifying
3q + -70 = q + 26

Reorder the terms:
-70 + 3q = q + 26

Reorder the terms:
-70 + 3q = 26 + q

Solving
-70 + 3q = 26 + q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1q' to each side of the equation.
-70 + 3q + -1q = 26 + q + -1q

Combine like terms: 3q + -1q = 2q
-70 + 2q = 26 + q + -1q

Combine like terms: q + -1q = 0
-70 + 2q = 26 + 0
-70 + 2q = 26

Add '70' to each side of the equation.
-70 + 70 + 2q = 26 + 70

Combine like terms: -70 + 70 = 0
0 + 2q = 26 + 70
2q = 26 + 70

Combine like terms: 26 + 70 = 96
2q = 96

Divide each side by '2'.
q = 48

Simplifying
q = 48

See similar equations:

| (x+3)*5-5=20 | | 2(5+3q)= | | 9w-7=8w-4 | | 2x^2+1=129 | | 5(y+7)=7*y+35 | | -2+5v=-27 | | 296.64=160+0.56x | | -2(3+9x)= | | (ln(9x+4))-(ln(x))=ln(10) | | W^2+5=36 | | 25x+30=45x+20 | | 4+a+3= | | 15w+17w-5+1=-3w+1-5 | | 2(y+8)=30-5y | | 2(3+9x)= | | -6y+3x^2=y-x+2 | | -5(x-4)=-73 | | 14w+17w-6+5=-5w+5-6 | | 9+10(6a-1)= | | 3b+2p=29.50 | | x+2x-2x+16=180 | | 35-4x=-10 | | (X-1)(9x^2+3x+1)=0 | | x+2x-x+16=180 | | -3(-7w+3)-6w=5(w-1)-8 | | 5N+34=2(1-9N) | | 10-5(6)=20 | | 5.1a+10=71.2 | | 0.25(4x-2)=x-.50 | | 8(x+4)=4(x+8)+4x | | 9x^4+27x^3-13x^2-12x+4=0 | | 10x+2y=54 |

Equations solver categories